Dynamical cooling of semiconductor by contact layer - Lipnicki, Zygmunt; Król, Fabian (International journal of heat and mass transfer, 2005)
The subject of this paper is the presentation of a simple theoretical model of cooling of a semiconductor. The problem of the unsteady behaviour both of the semiconductor and of the cold plate that are in touch by the contact layer was studied analytically. The influence of the parameters of the materials and the cooling conditions was investigated. The results in the form of an analytical formula and graphs are presented and the heat stream is compared with the experimental results.